Pink Dollars: Gay and lesbian Film Festivals and the Economy of Visibility - Rhyne, Ragan (2007)
This dissertation is about gay and lesbian film festivals, the first of which was founded in San Francisco in 1977 and subsequently served as a model for their international proliferation over the next thirty years. While the films programmed in these festivals have received a great deal of attention from scholars and critics, the festival institution itself has received less consideration. This dissertation narrates the history of gay and lesbian film festivals through an economic lens, asking how fundraising practices have been deployed in the community building projects of festivals, how the administrative structures of festivals as nonprofit organizations have been leveraged by the state toward the management of new social movements, and how these nonprofits have participated in the identification and cultivation of populations as niche markets by the commercial sector. This historical schema will offer an alternative model for understanding queer image production, not through a textual analysis of those images, but through an examination of the material circumstances of their circulation and distribution. This dissertation is not simply about the ways that community organizations like film festivals have been strategically engaged by the state and the market in the management and exploitation of gays and lesbians, it argues that gays and lesbians themselves have articulated their politics, artistic practice, and discourse of community within (and against) the parameters defined by the demands of organizational sustainability. Furthermore, this dissertation will illustrate why taking economic activity seriously as a part of the material practices of queer image production answers crucial questions about the ways that sexuality operates as a category of governance. The history of gay and lesbian film festivals, and their regulation through the administrative structures of the nonprofit sector, is part of a much larger history of political struggle and the development of new social movements over the past three decades.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Étude de la réception; 2-Étude des industries culturelles; 4-Amérique du Nord (lieu de production du savoir); _Nettoyé